Tingkat Pengetahuan Gizi Seimbang dan Gaya Hidup Pegawai Obesitas di Wilayah Kerja Kepolisian Resor Belitung Timur: Knowledge Of Balanced Nutrition And Lifestyle Of Obese Employees In The Working Area Of The East Belitung Resort Police - Putri Amiriya, Nabila; Devriany, Ade; Pertami Enardi, Ori (Svasta Harena: Jurnal Ilmiah Gizi, 2024)
Background: Obesity is a nutritional problem in the community caused by a lack of balanced nutrition knowledge and an unhealthy lifestyle. Nutritional knowledge and a healthy lifestyle influence a person's attitudes and behaviors. According to the 2023 Riskesdas, the prevalence of obesity in the Bangka Belitung Islands Province is 24.5%. Purpose: To identify the overview of the level of knowledge of balanced nutrition and the lifestyle of obese employees in the work area of the East Belitung Police. Methods: This study is a quantitative research with a descriptive research design involving 57 respondents selected using purposive sampling technique. The research data consists of primary data obtained from questionnaire responses, and secondary data including body weight and height obtained from the Health Clinic of East Belitung Police Resort. Results: In the workplace area of the Police Resort (Polres), employees classified as obese are predominantly male (94.7%), married (82.5%), and have completed high school education (73.7%). The average score for balanced nutrition knowledge is 57.06, categorizing it as sufficient, while the average lifestyle score is 83.30, indicating a good category. All employees fall into the central obesity category. Conclusion: Most of the respondents have sufficient knowledge of balanced nutrition and lead a healthy lifestyle. It is recommended to increase physical activity, especially  for police officers with overweight and obesity nutritional status.